2011
DOI: 10.1007/s10654-011-9614-1
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models for the study of HIV spread and control amongst men who have sex with men

Abstract: For a quarter of century, mathematical models have been used to study the spread and control of HIV amongst men who have sex with men (MSM). We searched MEDLINE and EMBASE databases up to the end of 2010 and reviewed this literature to summarise the methodologies used, key model developments, and the recommended strategies for HIV control amongst MSM. Of 742 studies identified, 127 studies met the inclusion criteria. Most studies employed deterministic modelling methods (80%). Over time we saw an increase in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 114 publications
(478 reference statements)
2
23
2
Order By: Relevance
“…Our sensitivity analysis (Appendix, section 6, http:// links.lww.com/QAD/A612) also confirmed that non-PHI infectiousness was one of the most important drivers of the epidemic, while PHI-related parameters were not among them. There were also a number of recent studies that arrived at similar findings [26][27][28][29]. A recent systematic review by Blaser et al [25] suggested that HIV transmission rate during PHI should be around 10 and 30 times higher than that of asymptomatic stage if PHI lasted, respectively, for 6 and 2 months.…”
Section: Discussionmentioning
confidence: 80%
“…Our sensitivity analysis (Appendix, section 6, http:// links.lww.com/QAD/A612) also confirmed that non-PHI infectiousness was one of the most important drivers of the epidemic, while PHI-related parameters were not among them. There were also a number of recent studies that arrived at similar findings [26][27][28][29]. A recent systematic review by Blaser et al [25] suggested that HIV transmission rate during PHI should be around 10 and 30 times higher than that of asymptomatic stage if PHI lasted, respectively, for 6 and 2 months.…”
Section: Discussionmentioning
confidence: 80%
“…Our analysis confi rmed the importance of implementation of a combination of interventions for eff ective HIV control in MSM. 13,17 The provision of PrEP as part of a combination strategy, even to a quarter of highly sexually active individuals, could prevent more than 7000 new HIV infections in the UK before the end of this decade. The relatively small coverage the programme requires is feasible because around half of Data are median (IQR), unless otherwise indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our previous study 3 suggested that undiagnosed HIV, repeat sexual partnerships, and young and high-activity MSM were the most important drivers of the HIV epidemic in UK MSM. Several interventions have been proposed in modelling studies 13 and have garnered interest. 14,15 We consequently formed and investigated seven individual HIV interventions: (1.1) test for HIV once a year; (1.2) test for HIV twice a year; (1.3) a test-and-treat programme assuming the ART initiation rate of those with CD4 count of less than 350 cells per μL to all diagnosed MSM regardless of CD4 count; (1.4) PrEP; (1.5) reducing the number of repeat sexual partners by 0•5 times; (1.6) reducing the number of one-off sexual partners by 0•5 times; and (1.7) reducing unprotected anal intercourse with repeat sexual partners by 0•5 times.…”
Section: Hiv Interventionsmentioning
confidence: 99%
“…Previous modeling reviews have been mostly narrative [44], [45]. We have tried to make our review as quantitative as possible, as well as assess study quality.…”
Section: Discussionmentioning
confidence: 99%